Science, technology and innovation culture - Chouteau, Marianne; Forest, Joëlle; Nguyen, Céline (Innovation, entrepreneurship, management series. Innovation in engineering and technology set, 2018)
We are facing unprecedented challenges today. For many of us, innovation would be our last hope. But how can it be done' Is it enough to bet on the scientific culture' How can technical culture contribute to innovation' How is technical culture situated with regards to what we name collectively the culture of innovation' It is these questions that this book intends to address.